UJI AKTIVITAS FRAKSI N-HEKSAN, ETIL ASETAT, ETANOL DAUN PARE (Momordica charantia L.) TERHADAP Staphylococcus epidermidis DAN Salmonella thypi - Muhammad Asri SR; Kasim, Rezky Amaliah; Suryanita (Akademi Farmasi Yamasi Makassar, 2025)
Bitter melon leaves (Momordica charantia L.) contain compounds such as flavonoids, saponins, triterpenoids, glycosides and alkaloids. This study aims to determine the difference in antibacterial activity of the N-hexane, Ethyl acetate and Ethanol 96% fractions fram bitter melon leaves (Momordica charantia L.) against the bacteria Staphylococcus epidermidis and Salmonella thypi. The research method is an experimental study to see the antibacterial activity of the N-hexane, ethyl acetate and etanol 96% fractions at concentrations of 5%, 10% and 15% using the disc diffusion method. The results of the research showed that Staphylococcus epidermidis bacteria obtained an inhibitory power of 5% (5,95 mm), 10% (12,23 mm), 15% (14,05 mm) for the N-hexane fraction. Ethyl acetate fraction 5% (6,08 mm), 10% (7,37 mm), 15% (10,93 mm). Ethanol fraction of 5% (6,37 mm), 10% (12,8 mm), 15% (13,98 mm). Salmonella thypi bacteria against the N-hexane fraction obtained an inhibitory power of 5% (7,83 mm), 10% (12,47 mm), 15% (13,88 mm). The ethyl acetate fraction is 5% (5,43 mm), 10% (10,85 mm), 15% (13,88 mm). Ethanol fraction of 5% (7,77 mm), 10% (10,27 mm), 15% (15,5 mm). It can be concluded that the N-hexane, ethyl acetate and ethanol 96% fractions have antibacterial activity.